Réponses

  • Omnes
  • Modérateur confirmé
2014-03-14T22:04:18+01:00
Salut,

A = t²+81+18t
A = t² + 18t + 81
A = (t+9)²

B= 4x²-4xy+y²
B = (2x)² - 2*2x * y + y²
B = (2x+y)²

C= 81+16y²-72y
C = 16y² - 72y + 81
C= (4y)² - 2 * 4y * 9 + 9²
C = (4y-9)²

D= x²+36-12x
D = x² - 12x + 36
D = x² - 2 * 6 * 1x + 6²
D = (x+6)²

E= m²+10m+25

E = m² + 2 * 5 * m + 5²
E = (m+5)²

Bonne soirée !


  • Utilisateur Brainly
2014-03-14T22:12:32+01:00
Factorise sais expressions :
A = t²+81+18t=(t+9)²
B= 4x²-4xy+y²=(2x-y)²
C= 81+16y²-72y=(9-4y)²
D= x²+36-12x=(x-6)²
E= m²+10m+25=(m+5)²